Makkunrai Values and Women’s Professional Identity: A Phenomenological Study of Ethical Leadership and Human Resource Management in South Sulawesi - Dipoatmodjo, Tenri Sayu Puspitaningsih; Arif, Hery Maulana; Latif, Abdul Halid (PT Maju Malaqbi Makkarana, 2025)
This qualitative study explores the embodiment of Makkunrai values among professional women in South Sulawesi and their influence on Human Resource Management (HRM) practices. Drawing upon indigenous wisdom from Bugis-Makassar culture, Makkunrai encapsulates virtues such as integrity, empathy, humility, and spiritual consciousness—values that subtly shape leadership behavior, workplace ethics, and interpersonal relationships. Using an interpretative phenomenological approach, this research involved in-depth interviews with ten professional women across various organizational contexts. The findings reveal that Makkunrai values not only reinforce ethical leadership and emotional intelligence but also serve as a moral compass guiding decision-making and conflict resolution within the workplace. Furthermore, the study highlights how these local values can harmonize with global HRM principles, creating a culturally grounded framework for sustainable human capital development. The integration of indigenous ethics with modern management systems provides both theoretical insights and practical implications for promoting inclusive, value-driven HRM in Indonesia’s evolving professional landscape.